Photobiomodulation therapy as a high potential treatment modality for COVID-19 - Soheilifar, Sepideh (Lasers Med Sci, 2020)
COVID-19 is now a worldwide concern, causing an unprecedented pandemic. The infected cases show different symptoms based on the severity of the disease. In asymptomatic and non-severe symptomatic cases, the host immune system can successfully eliminate the virus and its effects. In severe cases, however, immune system impairment causes cytokine release syndrome which eventually leads to acute respiratory distress syndrome (ARDS). In recent years, photobiomodulation (PBM) has shown promising results in reducing acute pulmonary inflammation. Considering the high potential impact of PBM on immune responses, we hypothesized that using PBM could be an effective treatment modality for ARDS management in COVID-19 patients.